Answers

The Brainliest Answer!
2016-01-17T12:47:51+05:30
{[(4x+7)²] + [(6x-1)²]} / {[(4x+7)²] - [(6x-1)² = 5/4
⇒ [(4x)² +7² +2(4x)(7) + (6x)² + 1² - 2(6x)(1)] / {(4x)² + 7² + 2(4x)(7) - [(6x)² +1² -      2(6x)(1)]}  =  5/4
⇒ [ 16x² +49 + 56x + 36x² +1 - 12x ] / [16x² + 49 + 56x -(36x² +1 - 12x )] = 5/4
⇒  (52x² - 12x +50 )/ (16x² +49 +56x - 36x² -1 +12x ) = 5/4
⇒   (52x² - 12x +50 ) / (-20x² +12x +48 ) = 5/4
⇒ 2(26x² - 6x +25) / 2( -10 + 6x +24) = 5/4 [cross multiplying]
⇒ 4(26x² - 6x +25) = 5(-10 + 6x +24)
⇒ 104x² - 24x + 100 = -50 + 30x + 120
⇒ 104x² - 24x +100 +50 -30x -120 = 0
⇒ 74x² - 54x -20 = 0
⇒ 2( 37x² - 27x - 10) = 0
⇒ 37x² - 27x -10 = 0
⇒ 37x² - 37x + 10x -10 = 0
⇒ 37x(x - 1) + 10(x - 1) = 0
⇒ (x-1)(37x+10) = 0
⇒ (x-1) = 0   or   (37x+10)  = 0
⇒ x = 1   or   37x = -10
⇒ x = 1   or    x = 10/37
∴ x = 1, 10/37
2 5 2